2021
DOI: 10.1007/s10648-021-09601-0
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Worries in Explaining the Link Between Test Anxiety and Test Performance

Abstract: The inverse relationship between test anxiety and test performance is commonly explained by test-anxious students’ tendency to worry about a test and the consequences of failing. However, other cognitive facets of test anxiety have been identified that could account for this link, including interference by test-irrelevant thoughts and lack of confidence. In this study, we compare different facets of test anxiety in predicting test performance. Seven hundred thirty university students filled out the German Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 69 publications
(114 reference statements)
0
4
0
1
Order By: Relevance
“…Physiological arousal refers to an automatic and bodily set of sensations (Joiner et al, 1999). Worry refers to the set thoughts regarding failure and its consequences of it (Liebert & Morris, 1967;Schillinger et al, 2021;Spielberger & Vagg, 1995). Cognitive interference occurs when negative beliefs about performance intrude on one's ability to concentrate (Eysenck & Calvo, 1992).…”
Section: Dimensions Of Test Anxietymentioning
confidence: 99%
“…Physiological arousal refers to an automatic and bodily set of sensations (Joiner et al, 1999). Worry refers to the set thoughts regarding failure and its consequences of it (Liebert & Morris, 1967;Schillinger et al, 2021;Spielberger & Vagg, 1995). Cognitive interference occurs when negative beliefs about performance intrude on one's ability to concentrate (Eysenck & Calvo, 1992).…”
Section: Dimensions Of Test Anxietymentioning
confidence: 99%
“…Also, test anxiety affects academic achievements negatively at any educational level [34]. There is a broad consensus empirically in the literature that test anxiety is strongly linked to poor academic performance [35], [36] extrapolated and reported that 20% of American students suffered lower academic performance due to test anxiety. Similarly, prevalence rate of test anxiety has been estimated around 20-25% of tertiary students' worldwide [37].…”
Section: Introductionmentioning
confidence: 99%
“…There are distinct but related notions on what constitutes test anxiety in the literature and existing measures of test anxiety differ in their conceptualisation of its facets. However, these conceptualisations usually centre on three dimensions: cognitive, emotional/physiological, and behavioural (see Schillinger et al, 2021 andUgwuanyi et al, 2020 for a review).…”
Section: Introductionmentioning
confidence: 99%